Manufactured fibers to fabrics and beyond - Ecklund, Roxanne (Insight Media, 2008)
Examines the origins, physical and chemical structures, properties, and uses of manufactured, or manmade, fibers. Covers rayon, lyocell, acetate, and such synthetic fibers as nylon, polyester, and acrylic.